Edukasi Kesadaran Diri tentang Kesehatan Mental bagi Pekerja Migran Indonesia di Taiwan - Martyana Dwi Cahyati; Emil Adly; Wahyu Widodo; Puji Harsanto; Ajeng Nova Dumpratiwi; Hung Wen-Yi; Nazwa Khairunnisa (Jurnal Surya Masyarakat, 2026)
The different culture and stress due to work is commonly faced by Indonesian migrant workers (PMI) live in Taiwan. To overcome these issues, this community service was conducted to enhance of self-awareness regarding mental health issues among Indonesian migrant workers in Taiwan. A survey was initially conducted by distributing a questionnaire as a pre-test to the respondents. Following this, an online Focus Group Discussion (FGD) was held to explore participants’ experiences and coping strategies. After that, a post-test was administered by distributing a follow-up questionnaire form to assess changes in participants’ understanding and awareness. The FGD revealed that while most participants have personal methods to manage stress. A post-test questionnaire demonstrated significant improvement in participants’ knowledge of mental health. This community service program revealed the importance of mental health education and the need to create safe spaces for dialogue among Indonesian migrant workers in Taiwan.